Aplikasi Mikoriza Glomus fasciculatum dan Glomus mosae dengan Tumbuhan Sorghum bicolor dalam Penyerapan Cr VI - Vini Kurnia Ramadhani; Sri Kasmiyati; Susanti Pudji Hastuti (Universitas Sebelas Maret, 2016)
Chrommium is a non-essential metal which is highly toxic to microorganisms and plants. One of the efforts to improve the productivity of the soil is done by inoculating the microorganisms in the soil, that is with using mycorrhizal fungi. Sorghum bicolor is a plant that quite often found in Indonesia and resistant to heavy metals, for the example is chromium. Research of the mycorrhizal association of Glomus fasciculatum or Glomus mosae with plants in reducing heavy metal contamination has been done, but the mechanism of resistance to heavy metals Cr VI in Sorghum bicolor which associated with mycorrhizal fungi Glomus mosae and Glomus fasiculatum has not been explained yet. The study was conducted experimentally using a randomized block design with three treatment concentrations of Cr VI (0 ppm, 5 ppm, 10 ppm) and 3 treatment mycorrhiza (without mikiroza; Glomus mosae; Glomus fasiculatum). Each treatment was made 5 replications. Plants kept in polybags arranged randomly. The study was conducted for one month, and the data were analyzed with ANOVA analysis with SPSS applications. The study aims to compare the effect of giving mycorrhizal Glomus Glomus fasiculatum and mosae to plant Sorghum bicolor on media contaminated with heavy metals chromium in various concentrations. The results showed that G.mosae and G.fasciculatum can increase plant tolerance to heavy metals. The presence of mycorrhizae cause the concentration of Cr VI is lower than in the absence of mycorrhiza on S.bicolor. There are significant differences between treatments without giving mycorrhiza and giving mycorrhiza (P ≤ 0.05). G. fasciculatum symbiotic with S.bicolor be able to reduce Cr VI more than G.mosae although the leaves has not significant difference.